2018
DOI: 10.1016/j.coal.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of oxidant stimulation for enhancing coal seam permeability: Effects of sodium hypochlorite oxidation on subbituminous and bituminous Australian coals

Abstract: A preliminary study of oxidant stimulation for enhancing coal seam permeability: Effects of sodium hypochlorite oxidation on subbituminous and bituminous Australian coals. Cogel (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…In this study, the majority of the new fractures and the void space were produced in the bright coal bands. The massive change occurred in the bright coal in this study conflicts with our previous finding that NaClO prefers to attack the dull coal than the bright coal when it flowed through the artificial cleats across both bright coal and dull coal [179]. To examine this confliction, the void space fractions for each coal before and after oxidation were analysed and we found that the NaClO oxidation seems to occur at the locations where high void space exists.…”
Section: Effect Of Oxidant Stimulation On Vertical and Horizontal Percontrasting
confidence: 92%
See 2 more Smart Citations
“…In this study, the majority of the new fractures and the void space were produced in the bright coal bands. The massive change occurred in the bright coal in this study conflicts with our previous finding that NaClO prefers to attack the dull coal than the bright coal when it flowed through the artificial cleats across both bright coal and dull coal [179]. To examine this confliction, the void space fractions for each coal before and after oxidation were analysed and we found that the NaClO oxidation seems to occur at the locations where high void space exists.…”
Section: Effect Of Oxidant Stimulation On Vertical and Horizontal Percontrasting
confidence: 92%
“…This tendency has been observed by researchers who tried to generate valuable organic acids from coal through NaClO oxidation [17,21]. The different reaction behaviours with different coal types were hypothesized to be related to key features in coal molecular structures and NaClO oxidative mechanisms [150]. Regarding coal molecular structure differences, the lower rank coals have been proposed to contain longer aliphatic side chains and more oxygen functional groups, while the higher rank coals are more aromatic with more poly-condensed structures [31,[122][123][124].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The majority of pore spaces in coals were micropores (less than 2 nm) and mesopores (2–50 nm), indicating that coal seam permeability is mainly controlled by fractures at different scales. Therefore, the stimulation methods focused on generating artificial fractures, oxidative dissolution of coal organic matter to improve natural fracture aperture, and mineral dissolution to remove occlusion and improve connectivity of natural fracture systems. Hydraulic fracturing and hydraulic slotting are the most common physical methods for generating fractures in coal seam. During the injection of high-pressure fluids and proppants for hydraulic fracturing, however, massive coal fines were always produced and may block the artificial fractures, , resulting in a serious reduction of fracture permeability. , The numerous fractures induced by stress release during hydraulic slotting have been proved to play a key role in improving methane extraction in underground coal mines.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Fluoride precipitation can occur easily in the presence of Ca and Mg ions. [13] Alternatively, Jing et al [3,14,15] proposed using a NaClO oxidant to increase the pore system connectivity or generate micro-structures in the matrix by dissolution. Such practice has also been reported by Yang et al [16,17] for enhancing permeability of shale formation.…”
Section: Introductionmentioning
confidence: 99%